PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DAN PERTUMBUHAN PERUSAHAAN - Agustami, Silviana; Rahman, Adrian (Program Studi Akuntansi FPEB UPI, 2015)
The research aims to determine how the influence of intellectual capital which measured by Value Added Intellectual Coefficient (VAIC) to finance performance which measured by Return on Asset (ROA) and Return on Equity (ROE) and to Firm Growth which measured by Asset Growth (AG) and Equity Growth (EG), in construction companiesÂ listed on the Indonesia stock exchange (IDX) 2011-2013 period .The sampling using purposive sampling method, the samples was taken from 7 companies. This research used secondary data, which means the data that used in this research come from annual report of company and is used smartPLS 3.0 to analysed the data. This research show that there is positive influence between intellectual capital to financial performance and intellectual capital also has positive influence to firm growth.Â